Konsep paradigma ekonomi Islam: kultur femonena paralel yang bermula dari sentimen agama menuju mode religius baru dalam skala global - Angga Eka Prasetya (FADZAT: Jurnal Ekonomi Syariah, 2022)
The purpose of this research is to present the concept of Islamic economic paradigm: parallel phenomena culture that starts from religious sentiment towards a new religious mode on a global scale. This study uses a qualitative descriptive-analytic approach. The data was collected by using literature study and documentation study. Data analysis using qualitative analysis approaches and techniques. The results of the study concluded: 1) Religion does govern business, offering a set of guiding principles and moral guidelines in business from a family scale to a global scale. 2) Faith is an Islamic business segmentation asset that provides the criteria and nature of prospects in business. 3) Religion is capable of being a vehicle for transformational social change in business. 4) Islamic economy has the structure and frame of reference for business culture by offering a new unit of analysis capable of demeaning the systems of capitalism and Marxism. 5) The contemporary approach of grounded Islamic economics is not a composite construction of capitalism through social interaction but a guide conferred in the name of rahmatan-lil-aalamiin